Comparison of resting-state alpha frequency and prefrontal cortex activation patterns between elite retired amateur boxers and healthy individuals: an fNIRS and EEG study - Muhammed Sıddık Çemç; Murat Kaldırımcı (Journal of Men's Health)
Background: The aim of this research is to investigate resting-state alpha frequency (α) of spectral powers (μV2) and cerebral activation changes in the prefrontal cortex (PFC) during the Stroop test in elite amateur boxers. The findings are compared with healthy individuals to evaluate the presence of chronic traumatic brain injury (CTBI). Methods: Electroencephalography (EEG) measurements were performed in the resting state with eyes open and closed. Functional Near Infrared Spectroscopy (fNIRS) recordings were taken from the PFC during the presentation of Stroop test stimuli to the participant in block form. Results: No significant difference was observed between the groups’ alpha frequency (α) of spectral powers (μV2). During the Stroop test congruent task, boxers showed significantly lower activation levels over the right dorsomedial prefrontal cortex (dmPFC) and during the incongruent task over the left dorsomedial prefrontal cortex (dmPFC) compared to the healthy control group. In addition, when the general activation during the Stroop test was examined, boxers also recorded a significantly lower activation level over the left dorsolateral prefrontal cortex (dlPFC)/ventrolateral prefrontal cortex (vlPFC)/ventromedial prefrontal cortex (vmPFC)/orbitofrontal cortex (OFC) compared to the healthy control group. No significant difference was detected regarding the Stroop test results. In conclusion, no difference was observed between boxers and healthy individuals regarding the alpha frequency of (α) spectral powers (μV2). However, during the Stroop test, boxers displayed significantly lower cerebral activation over the left and right dmPFC and left dlPFC/vlPFC/vmPFC/OFC compared to healthy individuals. Conclusions: This research has demonstrated that the brain activity of retired elite amateur boxers, particularly the activation levels in the PFC while the Stroop test is conducted, is lower compared to healthy individuals. The neurological health of athletes participating in contact sports such as boxing should be closely monitored, and larger-scale, long-term studies should be conducted to investigate the effects more thoroughly.